The family as an object of protection and a subject of law - Wojciech Lis (Journal of Modern Science)
Objectives The family is the basic social cell, the foundation of any social structure. The reason for the special treatment of the family is the functions it has to perform. However, despite the recognition of the uniqueness of the family, the wishful attitude to it is not always confirmed by normative solutions. The purpose of the study is to attempt to identify provisions that speak in favor of recognizing the subjectivity of the family.